Biomonitoring of metal levels in urban areas with different vehicular traffic intensity by using Araucaria heterophylla needles. (October 2020) - Alexandrino, Katiuska; Viteri, Fausto; Rybarczyk, Yves; Guevara Andino, Juan Ernesto; Zalakeviciute, Rasa
Highlights: Araucaria heterophylla needles is successful as biomonitor. Ca, Mg and K are associated with natural emissions rather than with road-traffic emissions. Typical geological elements (Mn, Fe and Al) are correlated with traffic-related metals. Decelerating activities are the main source for vehicle non-exhaust emissions. Green areas can reduce the pollutants concentration. Abstract: For the first time, Araucaria heterophylla needles were used as a biomonitor to assess the concentration of metals in urban areas. The samples were collected in the Andean city Quito, in Ecuador, from sites with high, moderate and low vehicular traffic intensity. Then, the concentrations of Ca, K, Mg, Mn, Fe, Al, Ba, Zn, Cu, Cr, Pb and Co were measured by using an Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). Source apportionment was studied employing Principal Component (PCA) and Pearson analyses. Ca, K, and Mg were identified to come from natural sources, showing the highest levels. On the other hand, Mn, Fe and Al were related to both natural and road traffic emissions, while Ba, Zn, Cu, Cr, Pb and Co were only related to road traffic emissions. The decelerating activities were identified as the main source for vehicle non-exhaust emissions in the area of study. Areas with the highest vulnerability in metal emissions from vehicular traffic in the city of Quito were also identified through Geographic Information System. Alarming concentrations of traffic-related metals near a pediatric hospital were revealed. It was observed that streets located near a green area such as urban park, even with high or moderate traffic intensity, may experience reduced concentrations of pollutants. This work showed that Araucaria heterophylla needles are suitable for monitoring metals associated with road traffic emissions in areas with different vehicular traffic intensity.